Efforts to Overcome Reading and Writing Difficulties in Providing Study Guidance for Class II Primary School Students - umayah, Urip (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
The aim of this research is to determine the extent of teachers' efforts to overcome difficulties in learning to read and write in class II students at SDN Slarang 03. This research uses a qualitative descriptive writing approach. The data obtained in this research include: efforts made by class IV teachers to overcome difficulties in learning to read and write experienced by students and supporting factors and factors inhibiting teachers in overcoming difficulties in learning to read and write. Data was taken by observing the process of teaching and learning activities, interviews with class II teachers and documentation. This research finds out that the efforts made by class II teachers to overcome the difficulties in learning to read and write experienced by students are by using varied learning methods, creating a conducive and creative learning atmosphere, and tutoring. Supporting factors for teachers in overcoming difficulties in learning to read are teachers' patience in teaching, the principal who always provides support for the efforts made by the teacher. Meanwhile, inhibiting factors are students' experiences at school, students' experiences at home, attention from parents and the influence of television and cell phones. With the efforts made by students who were unable to read and write when they first entered, they are now able to read and write by regularly providing study guidance.